MacGregors: serena & caine - Roberts, Nora (Richmond Silhouette, 1985)
Nora Roberts has enchanted millions with her powerful, passionate stories. Now be swept away by the MacGregor clan.Playing the Odds - Serena MacGregor was on her own and looking for a challenge. She found it in the arms of roguish gambler Justin Blade. His charm and ruthless good looks invaded her every waking moment, but she was wary of a man who seemed to have secrets to hide...Tempting Fate - Lawyer Caine MacGregor had a reputation for being a demon in the courtroom - and in the bedroom. He yearned to break down Diana Blade's icy wall of control and release the passionate woman within. Could he entice her to risk everything for the love of a MacGregor?
Keywords: English Fiction